Lokalny Program Rewitalizacji. Adaptacje zabudowy pofabrycznej w centrum Łodzi - Krzysztofik, Sylwia (Lodz University of Technology Press, 2016)
Łódź is city where the collapse of the textile industry caused galloping unemployment. Better off residents tend to isolate themselves from less affluent social groups – in city centres the formed poverty enclaves. Next step was expanding urbanized area over the areas around the city and the outflow of better-off residents from the city centre to the suburbs. Lack of investment in the centre entailed gradual degradation - buildings have very bad technical condition, problem is also low intensity of inner urban areas and the demolition of entire quarters. Revitalization downtown area is one of main creating an urban policy. In Łódź in July 2004 was adopted „Simplified local revitalization program for selected areas of downtown in Łódź for the years 2004-2013”, called Local Revitalization Program. It is document describing the development strategy for the city, in which central area of Łódź has been recognized as area with the highest concentration of spatial and social problems. This document describes the necessary action, which may lead to the development and improvement of the image of the city and allow the municipal government and other entities to apply for EU funds for investments revitalization. Particularly important for the preservation of the identity of Łódź are investment activities in the post-industrial areas. In the design of the pilot program provided for three projects on building components post-industrial. In the centre of Łódź there are post-industrial areas, abandoned and subjected to gradual degradation. The way to activate them is micro-interventions – initiatives aimed at space recovery and adaptation of buildings to the needs of new users within a short time with the involvement of a small budget. These processes are spontaneous or result from a deliberate desire to create a new space. One of the ways to take advantage of such objects may be their adaptation on a temporary basis by introducing new features. Large areas can be treated as an asset and adapted by new users, if certain imperfections of the location are accepted. Micro-initiatives may be consistent with the spatial policy of the city and support the planned direction of changes in urban spaces. These are changes that do not require the involvement of a large budget. A great advantage of micro-initiatives is that it does not take a long time to put the idea into practice and there is a possibility of rapid temporary uses in changing conditions. Places that undergo these changes are discovered by the residents anew and are seen by them in a different light. Urban acupuncture gives perceptible effect with the available resources reached in a very short time.
Local Revitalization Program. Adaptations of post-industrial buildings in the centre of Łódź
Keywords: revitalization urbanized areas; revitalization process; rewitalizacja obszarów zurbanizowanych; proces rewitalizacji